The Central African Republic's Infrastructure : A Continental Perspective - Domínguez-Torres, Carolina; Foster, Vivien (World Bank, Washington, DC, 2017)
Between 2000 and 2005 infrastructure made a modest net contribution of less than one percentage point to the improved per capita growth performance of the Central African Republic (CAR), despite high expenses in the road sector. Raising the country's infrastructure endowment to that of the region's middle-income countries could boost annual growth by about 3.5 percentage points. Assuming that the inefficiencies are fully captured, comparing spending needs against existing spending and potential efficiency gains leaves an annual funding gap of $183 million per year. By far the largest gap exists in transport. The CAR has the potential to close this gap by raising additional public funding for infrastructure from increased fiscal receipts of various kinds. Furthermore, the CAR has not captured as much private finance for infrastructure (measured as a percentage of Gross Domestic Product, or GDP) as many of its neighbors. This scope for improvement, coupled with the prospect of an economic rebound and prudent policies, could lift the country from it fragile state back to and beyond the prosperity standards it once enjoyed.